KEANEKARAGAMAN GASTROPODA DAN BIVALVIA HUTAN MANGROVE SEBAGAI MEDIA PEMBELAJARAN PADA KONSEP KEANEKARAGAMAN HAYATI KELAS X SMA - Elya Febrita '; Darmawati ' '; Jasmi Astuti ' (Biogenesis, 2015)
To investigate the diversity of gastropods and bivalves in the mangrove forest area Apit Siak River District in April to December2014.The results are used for the development of instructional mediain the form of media objects directly in the form of wet preservation of the species are found. This research was carried out with 2 phases: phase field research and media development. Determination of the research station by purposive sampling to establish three research stations. Each station consists of two transects and one achtransect consists of 3 plots. Biological parameters observed that diversity index and the physical and chemical parameters include salinity, pH, temperature, organic content of the substrate and the texture class. The results showed that the diversity of gastropods in the mangrove forest area Apit Siak River District ranged from 1.73 to 1.85 which is relatively moderate range. The results of the research can be used as a medium of learning in the from of media preservation of biodiversity o the material wet grade ten high school.Keywords : diversity Gastropoda, bivalves, mangrove, media learning.